Pelaksanaan Supervisi Akademik Pengawas Dalam Meningkatkan Kompetensi Profesional Guru Pendidikan Agama Islam Pada SMP Negeri Di Kabupaten Lembata Nusa Tenggara Timur - Abdurahman S. Sarabiti (Tambur : Journal of Music Creation, Study and Performance, 2021)
A scientific review that aims to increase the knowledge and insight of Islamic Religious Education supervisors in academic supervision by examining from a perspective how important the presence of a supervisor is in improving the professional competence of Islamic Religious Education teachers in the Lembata Regency. The method used is in the form of literature review and simple observations and interviews through a series of activities related to the methods of collecting library data, reading and taking notes, as well as managing research materials sourced from book reviews and simple observations from supervisory documents. The results of this study are expected to provide policy changes. For the Regional Government and the Ministry of Religion of the Lembata Regency, precisely in Islamic Religious Education, both regarding the recruitment of supervisors, equitable distribution of supervisors' placement, and increasing the intensity of supervisory development. The results of this study are also expected to be an internal correction for supervisors and used as evaluation material regarding the competence of academic supervision of supervisors in fostering Islamic Religious Education teachers at State Junior High Schools in Lembata Regency, in order to obtain competent and professional supervisors, the competent authorities should recruit supervisors. Following applicable regulations.